Atrophic vaginitis: symptoms, diagnosis and treatment - Wielgoś, Mirosław; Mazanowska, Natalia; Pietrzak, Bronisława (Menopause Review/Przegląd Menopauzalny, 2013)
Improvement of living conditions and advances in medicine throughout the last few decades have led to prolonged life expectancy. Unfortunately, inevitable physiological processes of ageing cause burdensome changes responsible for worsening of the quality of life of postmenopausal women. Many of these changes are linked to the loss of ovarian hormonal activity. Complaints resulting from a decline in the estrogen level and symptoms involving the lower genitourinary tract in postmenopausal women usually progress with time. They emerge from loss of vaginal epithelium thickness and elasticity, increase in pH of vaginal discharge as well as shift from physiological vaginal microflora with prevailing Lactobacillus spp. to abnormal milieu with dominance of other frequently anaerobic microorganisms. To relieve often severe symptoms of urogenital atrophic changes non-hormonal as well as hormonal treatment methods are available. Vaginal moisturizers and lubricants as well as systemic hormone therapy are treatment options to be considered. Local estrogen therapy remains the first choice therapy in women with no contraindications to estrogen administration. It is an effective and safe method of relieving symptoms of urogenital atrophy. There are different preparations of estrogens for local therapy available. A combination of estrogen and Lactobacillus cultures is an option worth considering. Early treatment allows for maintaining healthy vaginal microflora, which prevents development of distressing symptoms that decrease the quality of life.